2000
DOI: 10.1037/1040-3590.12.3.346
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the factor structure of the AUDIT.

Abstract: This study investigated the Alcohol Use Disorders Identification Test's (AUDIT) factor structure and psychometric properties. The factor structure was derived from a sample of 7,035 men and women primary care patients. A principal components analysis identified 2 factors in the AUDIT data and was supported in a confirmatory factor analysis (CFA). The 2 factors were Dependence/Consequences and Alcohol Consumption. The CFA also provided support for a 3-factor model whose factors (Alcohol Consumption, Alcohol Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 13 publications
3
100
0
2
Order By: Relevance
“…Em estudos, realizados em amostras de indivíduos adultos da Espanha e Nova Iorque, o AUDIT apresentou coeficiente α-Cronbach de 0,93 e 0,85, respectivamente (44)(45) . Pesquisadores dos Estados Unidos e Coreia, ao avaliarem estudantes universitários, encontraram coeficiente α-Cronbach de 0,94 e 0,85, respectivamente (46)(47) .…”
Section: Discussionunclassified
“…Em estudos, realizados em amostras de indivíduos adultos da Espanha e Nova Iorque, o AUDIT apresentou coeficiente α-Cronbach de 0,93 e 0,85, respectivamente (44)(45) . Pesquisadores dos Estados Unidos e Coreia, ao avaliarem estudantes universitários, encontraram coeficiente α-Cronbach de 0,94 e 0,85, respectivamente (46)(47) .…”
Section: Discussionunclassified
“…16 Scores on the AUDIT range from 0-40, and scores greater than 8 indicate high-risk for hazardous and harmful alcohol use; 17 specificities were between 0.80 and 0.90 18 (alpha = 0.90). Participants also indicated whether they had used cannabis, cocaine, amphetamine, or other drugs in the previous 4 months (yes/no).…”
Section: Measures Computerized Interviewsmentioning
confidence: 99%
“…Current alcohol consumption was also assessed using the 3-item Alcohol Use Disorders Identification Test (AUDIT-C). [22][23][24] Persons were classified as having hazardous alcohol use if they drank in the past year and their total score was four or greater. If participants reported that they drank six or more drinks in one sitting at least once a month, they were classified as engaging in binge drinking.…”
Section: Confoundersmentioning
confidence: 99%